Predictors of invasive mechanical ventilation in hospitalized COVID-19 patients: a retrospective study from Jordan. Issue 8 (3rd August 2022) - Kabbaha, Suad; Al-Azzam, Sayer; Karasneh, Reema A.; Khassawneh, Basheer Y.; Al-Mistarehi, Abdel-Hameed; Lattyak, William J.; Aldiab, Motasem; Hasan, Syed Shahzad; Conway, Barbara R.; Aldeyab, Mamoon A.
ABSTRACT: Objectives: To identify early indicators for invasive mechanical ventilation utilization among COVID-19 patients. Methods: This retrospective study evaluated COVID-19 patients who were admitted to hospital from 20 September 2020, to 8 August 2021. Multivariable logistic regression and machine learning (ML) methods were employed to assess variable significance. Results: Among 1, 613 confirmed COVID-19 patients, 365 patients (22.6%) received invasive mechanical ventilation (IMV). Factors associated with IMV included older age >65 years (OR, 1.46; 95%CI, 1.13–1.89), current smoking status (OR, 1.71; 95%CI, 1.22–2.41), critical disease at admission (OR, 1.97; 95%CI, 1.28–3.03), and chronic kidney disease (OR, 2.07; 95%CI, 1.37–3.13). Laboratory abnormalities that were associated with increased risk for IMV included high leukocyte count (OR, 2.19; 95%CI, 1.68–2.87), low albumin (OR, 1.76; 95%CI, 1.33–2.34) and high AST (OR, 1.71; 95%CI, 1.31–2.22). Conclusion: Our study suggests that there are several factors associated with the increased need for IMV among COVID-19 patients. These findings will help in early identification of patients at high risk for IMV and reallocation of hospital resources toward patients who need them the most to improve their outcomes.